2020
DOI: 10.3390/dj8010008
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Maternal Reports of Young Children’s Dental Disease Status: Avon Longitudinal Study of Parents and Children

Abstract: Background: Parental reports of their children’s health status is integral to pediatric medical and dental care. Therefore, understanding the accuracy of such reports is vital. Our objectives were to (1) assess the correlation between maternal reports of their children’s indicators of caries experience (subjective assessment) and actual caries status determined by oral examination (objective assessment), and (2) identify potential modifiers of this correlation. Methods: Longitudinal data from the Avon longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Accuracy may be higher for younger children and children with dental insurance (Snell et al 2019). Poor oral health ratings more accurately reflect treatment needs than good oral health ratings, and parents commonly fail to consider the possibility of poor oral health for their children or ignore caries experience that would prompt concern from dental professionals (Talekar et al 2005;Divaris et al 2012;Akinkugbe et al 2020). Parental ratings often also differ from child self-ratings.…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy may be higher for younger children and children with dental insurance (Snell et al 2019). Poor oral health ratings more accurately reflect treatment needs than good oral health ratings, and parents commonly fail to consider the possibility of poor oral health for their children or ignore caries experience that would prompt concern from dental professionals (Talekar et al 2005;Divaris et al 2012;Akinkugbe et al 2020). Parental ratings often also differ from child self-ratings.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective ratings of oral health can be used as valid surrogates of permanent caries experience [Thomson et al, 2012] or used as a caries risk assessment tool in the case were no clinical dental data (dmfs/dmft) are available. Some studies have shown modest associations between parents' ratings and children's oral disease status [Divaris et al, 2012;Akinkugbe et al, 2020]. Such findings might be explained by the fact that subjective health ratingssubject to personal and sociocultural factorscan taint by either magnifying or diminishing the individual perceptions of health and wellbeing [Jylhä, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient weight gain during gestation has been correlated with an elevated likelihood of preterm birth and reduced birth weight among infants [18]. Furthermore, infants affected by these conditions have been observed to be at an augmented risk of developing enamel defects in their primary dentition [13,19]. Throughout pregnancy, it is imperative for expectant mothers to maintain a well-rounded and nutritionally balanced diet to adequately address both maternal and fetal nutritional requirements.…”
Section: Discussionmentioning
confidence: 99%